Multivariate genomewide linkage scan of neurocognitive traits and ADHD symptoms: Suggestive linkage to 3q13 - Doyle, Alysa E. (2008)
Family and twin studies suggest that a range of neurocognitive traits index the inherited liability to ADHD; however, the utility of such measures as endophenotypes in molecular genetic studies remains largely untested. The current paper examined whether the inclusion of neurocognitive measures in a genomewide linkage analysis of ADHD could aid in identifying QTL linked to the behavioral symptoms of the condition. Data were from an affected sibling pair linkage study of DSM-IV ADHD conducted at Massachusetts General Hospital. The sample included 1,212 individuals from 271 families. ADHD symptoms were assessed with the K-SADS-E. The neurocognitive battery included Wechsler Intelligence Scales subtests, the Stroop, the Wisconsin Card Sorting Test (WCST), the Rey Osterreith Complex Figure, a working memory CPT, the CVLT and WRAT-III subscales. Evidence for linkage was assessed using a simulation-based method that combines information from univariate analyses into the equivalent of a multivariate test. After correction for multiple trait testing, a region on chromosome 3q13 showed suggestive linkage to all neurocognitive traits examined and inattention symptoms of ADHD. The second highest peak occurred on 22q12 but showed linkage to a single subscale of the WCST. In univariate analysis, this region retained criteria for suggestive linkage to this measure after correction for multiple trait testing. Our primary findings raise the possibility that one or more genes on 3q13 influence neurocognitive functions and behavioral symptoms of inattention. Overall, these data support the utility of neurocognitive traits as ADHD endophenotypes, but also highlight their limited genetic overlap with the disorder.